Treatment of burns using polyethylene-glycol-based drugs: Dynamics of regeneration at the biochemical, cytological, histological, and organism levels of organization - Zazharskyi, V. V.; Zaslavskyi, O. M.; Sosnickyi, O. I.; Tishkina, N. M.; Zazharska, N. M.; Biben, I. A.; Sosnicka, A. O.; Brygadyrenko, V. V. (Regulatory Mechanisms in Biosystems, 2024)
Every year, up to 11 million burns are recorded. They are first among all traumas, leading to over 300,000 deaths around the globe every year. Burns caused by fire are also one of the main causes of deaths and disability-adjusted life years in countries with low and average levels of income. This research analyzed an experimental modeling of burn treatment using anti-burn drugs. Laboratory guinea pigs were traumatized with 2–3 degree burns with the burnt area of 15–20% of the skin surface. We compared the therapeutic efficacies of the experimental drug based on polyethylene glycol and the officinal medicinal drug – the ointment Pantestin. We assessed pathophysiological and pathomorphological changes over the process of burns, microbial landscape on the skin and in the microbiome of the internal environment of the guinea pigs. The most effective drug was the experimental anti-burn ointment based on polyethylene glycol. On the third day of the experiment, the Pantestin drug ensured the survival of 14.7% of the experimental animals compared with 57.1% survival using the ointment of the experimental drug and 100% death of the control animals that received no anti-burn therapy. The dominant bacterial pathogens that induce pathogenesis of the burn process are purulent-necrotic and toxicogenic ubiquitous prokaryotes Pseudomonas aeruginosa, hemolytic capsular variant of Escherichia coli, and Staphylococcus aureus. From the burn wound, various prokaryotic microflora were isolated, and since day three after the infliction of the burn, in microbiome of the large intestine, no more indigenous bioindicators of the macroorganism’s physiological wellbeing – Aerococcus viridans and Mycobacterium vaccae, were isolated against the background of rapid decrease in isolation of lactobacteria, bifidobacteria, and saccharolytic yeasts.